Involvement of metalloproteinase and nitric oxide synthase/nitric oxide mechanisms in early decidual angiogenesis–vascularization of normal and experimental pathological mouse placenta related to maternal alcohol exposure - Gualdoni, Gisela Soledad; Barril, Camila; Jacobo, Patricia Verónica; Pacheco Rodríguez, Liliana Nazareth; Cebral, Elisa (Frontiers in Cell and Developmental Biology, 2023)
Successful pregnancy for optimal fetal growth requires adequate early angiogenesis and remodeling of decidual spiral arterioles during placentation. Previous to initiation of invasion and endothelial replacement by trophoblasts, interactions between decidual stromal cells and maternal leukocytes, such as uterine natural killer (uNK) cells and macrophages, play crucial roles in the processes of early maternal vascularization, such as proliferation, apoptosis, migration, differentiation, matrix and vessel remodeling. These placental angiogenic events are highly dependent on the coordination of several mechanisms at the early maternal-fetal interface, one of them are the expression and activity of matrix metalloproteinases (MMPs) and endothelial nitric oxide synthases (NOS). Inadequate balances of MMPs and nitric oxide (NO) are involved in several placentopathies and pregnancy complications. Since alcohol consumption during gestation can affect fetal growth associated with abnormal placental development, recently, we showed, in mouse, that perigestational alcohol consumption (PAC) up to organogenesis induces fetal malformations related to deficient growth and vascular morphogenesis of the placenta at term. In this review, we summarize the current knowledge of the early processes of maternal vascularization that lead to formation of definitive placenta, and the roles of angiogenic MMP and NOS/NO mechanisms during normal and altered mouse early gestation. Then, we propose hypothetical defective decidual cellular and MMP and NOS/NO mechanisms involved in abnormal decidual vascularization induced by PAC in an experimental mouse model. This review highlights the important roles of decidual cells and their MMP and NOS balances in the physiological and pathophysiological early maternal angiogenesis-vascularization during placentation in mouse.